Photovoltaic and Impedance Spectroscopic Analysis of CdSe Quantum Dot Solar Cell - Farooq, W. A.; Fatehmulla, Amanullah; Aslam, M.; Atif, M.; Ali, Syed Mansoor; Yakuphanoğlu, Fahrettin; Yahia, I. S. (Amer Scientific Publishers, 2014)
Impedance spectroscopy is a very strong tool for the characterization of photovoltaic devices. We have fabricated a CdSe quantum dot sensitized solar cell based on three layers of nanostructure Tio(2) on FTO and blended with iodine based electrolytes. Photovoltaic properties and impedance spectroscopic analysis of the solar cell are performed using sc-4200 characterization system. We have achieved a short circuit current density of 0.26 nna/cm(2) and an open circuit voltage of 0.57 V under AM1.5. The capacitance voltage, the conductance voltage, and the series resistances voltage characteristics of the quantum dot solar cell are measured in the frequency range of 5 khz to 3 nnhz. At 5 kHz maximum capacitance is 28 nnicrofarad with bias voltage of 1 v. It decreases sharply at 500 kHz and goes to negative value after 700 kHz. This behavior is due to injection of electrons from the fto electrode into nanostructured layers of Tio(2). The present investigations are useful for the development of quantum dot sensitized solar cell.
Keywords: Nano Structured; Impedance Spectroscopy; Photovoltaic; Quantum Dot